Enlarging ovarian cysts mimicking malignant or borderline tumors during pregnancy - Yibo Dai; Guoli Liu; Yan Wang; Jun Wei; Zhiqi Wang; Jianliu Wang (BMJ Publishing Group, 2021)
Background: Ovarian cysts are uncommon gestational complications. Because of high-level progesterone, ovarian endometriomas may undergo decidualization during pregnancy, manifesting as enlarging cysts with papillae and rich blood flow. Such cases can mimic malignant or borderline tumors, causing dilemmas in clinical management. Here, we present two cases of enlarging ovarian cysts during pregnancy with evidence suggesting decidualized endometrioma. The diagnosis and treatment are further discussed, which add to our limited knowledge and might help future clinical practice. Case summary: In the first case, a right ovarian cyst was detected by ultrasound in a 32-year-old pregnant woman. The cyst measured 4.2 cm in diameter at 7+6 weeks of gestation, and gradually increased to 9.6 cm ​× ​7.6 cm ​× ​5.6 cm at 37+5 weeks, with multiple solid papillae lining the inner wall. During cesarean section, an ovarian mass of approximately 9 cm in diameter was surgically removed, which was later identified by pathological review as an endometrioma with decidualization. The second case also presented as an enlarging ovarian mass during the first and second trimester. The size of the cyst peaked at 24+5 weeks of gestation, measuring 6.9 cm ​× ​5.6 cm ​× ​4.1 cm. But in the third trimester, the tumor slightly regressed. Careful follow-up was adopted after successful vaginal delivery, and the cyst was found to have undergone quick regression shortly after pregnancy. Both patients recovered well after delivery with no further complications. Conclusion: Endometriomas with decidualization during gestation may resemble borderline or malignant tumors. Close monitoring and proper management are essential for guiding clinical management.